Designation of a neotype for Myxicola infundibulum (Montagu, 1808) (Annelida: Sabellidae) and a new species from the UK - Teresa Darbyshire (European Journal of Taxonomy, 2023)
The historical context of Myxicola species identification, around the UK and Europe, is reviewed and confusion surrounding the type species for the genus, Myxicola infundibulum (Montagu, 1808), discussed. Myxicola infundibulum is re-described and a neotype designated. A new species, M. polychroma sp. nov., is also described from the UK and is discussed, along with M. infundibulum, in relation to historical synonymised species from the region as well as current species known worldwide. Genetic and morphological details are provided for both species to aid in distinguishing them and determining the validity of other taxa in the future. Myxicola polychroma sp. nov. is distinguished through a combination of non-differentially coloured radiole tips, long, fine pinnulae that terminate below the lower margin of the basal membrane, large, fleshy, triangular radiolar appendages that arise centrally, interramal eyespots, dense, fine notochaetae and uncini with upper teeth 0.6–0.8 × length of the main fang. The type specimens of Myxicola steenstrupi Krøyer, 1856 and the status of that species are also discussed.